Airborne flux measurements of methane and volatile organic compounds over the Haynesville and Marcellus shale gas production regions. Issue 12 (26th June 2015) - Yuan, Bin; Kaser, Lisa; Karl, Thomas; Graus, Martin; Peischl, Jeff; Campos, Teresa L.; Shertz, Steve; Apel, Eric C.; Hornbrook, Rebecca S.; Hills, Alan; Gilman, Jessica B.; Lerner, Brian M.; et al.
Abstract Emissions of methane (CH4) and volatile organic compounds (VOCs) from oil and gas production may have large impacts on air quality and climate change. Methane and VOCs were measured over the Haynesville and Marcellus shale gas plays on board the National Center for Atmospheric Research C‐130 and NOAA WP‐3D research aircraft in June–July of 2013. We used an eddy covariance technique to measure in situ fluxes of CH4 and benzene from both C‐130 flights with high‐resolution data (10 Hz) and WP‐3D flights with low‐resolution data (1 Hz). Correlation (R = 0.65) between CH4 and benzene fluxes was observed when flying over shale gas operations, and the enhancement ratio of fluxes was consistent with the corresponding concentration observations. Fluxes calculated by the eddy covariance method show agreement with a mass balance approach within their combined uncertainties. In general, CH4 fluxes in the shale gas regions follow a lognormal distribution, with some deviations for relatively large fluxes (>10 µg m−2 s−1). Statistical analysis of the fluxes shows that a small number of facilities (i.e., ~10%) are responsible for up to ~40% of the total CH4 emissions in the two regions. We show that the airborne eddy covariance method can also be applied in some circumstances when meteorological conditions do not favor application of the mass balance method. We suggest that the airborne eddy covariance method is a reliable alternative and complementary analysis method to estimate emissions from oil and gas extraction.